The activity antibiofilm of betadine leaf (Jatropha multifida Linn) juice on urinary catheters - Tania, Rada; Gunardi, Wani Devita; Sudradjat, Susana Elya (Published by Universitas Gadjah Mada, 2025)
Biofilm formation can reduce the efficacy of antibiotics against pathogenic microorganisms. Flavonoids are proven to have antibiofilm activity. Betadine leaf (Jatrophas multifida Linn) contains abundant flavonoids. This study aimed to evaluate the biofilm activity of the betadine leaf juice on urinary catheters. Biofilm forming Escherichia coli was isolated from a urinary catheter. The betadine leaf juice was prepared by harvesting, washing, drying, juicing, centrifuging, and sterilizing the juice. Phytochemical analysis was performed to identify the presence of steroids, alkaloids, flavonoids, and phenols. Biofilm and antibiofilm assays were conducted by incubating thioglycolate medium with varying concentrations of the betadine leaf juice and E. coli suspension, with bacterial growth and biofilm formation assessed based on turbidity observations. Alkaloids, steroids, flavonoids, and phenolic compounds have been found in the sterilized betadine leaf juice. Bacterial growth was observed in all tubes containing different dilutions of the betadine leaf juice. However, turbidity levels increased as the juice concentration decreased. Additionally, the weight of the urinary catheter was significantly greater in tubes with lower juice concentrations (p=0.02). In conclusion, the J. multifida Linn leaf juice has potential antibiofilm activity against E. coli in urinary catheters.